Imidacloprid, a chemistry tool of the future within an integrated management of green house whiteflies - OROZCO, OLGA LUCIA; ABELLA, FERNANDO; PINZON, CAMILO (Revista Colombiana de Entomología, 1995)
The greenhouse whitefly Trialeurodes vaporariorum (Westwood) is one the most important insect pests in horticulture, ornamental and fruit crops. Adequate management as the use of threshold levels, specific and rational application of insecticides is essential. Several trials were carried out in the Sumapaz region, in Colombia, since 1987 against T vaporarionun, a key pest of snap beans (Phaseolus vulgaris). These trials demonstrated the powerful insecticide action of Imidacloprid (NTN 33893). Imidacloprid, a novel substance with a different action and mechanism related to the chloronicotinic nitroguanidines compounds, was used as a seed dressing (Imidacloprid WS 70) and showed interesting degree of protection until 35 days, afterward was completed by sprays with foliar applications (Imidacloprid SC 350). Another alternative was the granulated formulation (Imidacloprid GR 5) which was spread on the row at planting; Chis treatment showed an interesting degree of protection until 55 days. The start of the foliar application depended on the threshold levels established by ICA-CIAT. The preparation can be used in a broad range of agriculturally important crops, furthermore, it has a different biochemical target, high systemic action, low toxicity, and is effective against sucking insects such as T. vaporariorum; important characteristics within an Integrated Pest Management Program.